Business Model Canvas : Yeppo / Hanis Shafinaz Shaharudin ... [et al.] - Shaharudin, Hanis Shafinaz; Ahmad Shahril, Nur Alia; Suhaimi, Nurul Afiqah Batrisyia; Dzulkifli, Nurul Izzanie; Mohammad Samahani, Wan Muhammad Lutfi (2021)
YEPPO is a newly developed small company and the name Yeppo itself is means pretty in Korean and this is suitable with the youthful since our products are targetted to young people. Our company has produces modern talcum in the form of liquid. We have modernized it inspired by the routine use of the ancients who always used bedak sejuk to maintain their facial beauty. Besides, it suitable with the current situation, when everybody have their own career and busy, so that this innovation could be the best for them in taking care their face since we used natural ingredients for our products. Our company has put the mission to maintain and produce high quality products that can solve our customers’ problems. Besides, the vision is to be one of well-known local skincare product in Malaysia and supply our liquid scented bedak sejuk worldwide by 2030. Because of that, we need to be up to date from time to time to move along with other developed skin care products in Malaysia. Yeppo has provide portable business that can go without physical business. This can make the customers are easily to get our products because they can go for online shop to purchase it. So that, they can order it at any time or everywhere. But on the other side, because of we are a new brand in the industry, we are lack of experience and has little market presence and reputation in industry. Hence we will focusing on doing marketing in online platform since people nowadays especially young adults are active in using social media such as Instagram. Besides, we need to compete with other well-known skin care products such clay mask as a better version of facial powder bedak sejuk. Then, for compete and making name in skin care industry in Malaysia, we had made an organize plan through Business Model Canvas as a tool of strategy to develop our company. Plus, there are nine elements in the Business Model Canvas (BMC) that we need to focusing of such as value proposition, customer segments, channel, customer relationship, revenue streams, key activities, key resources, key partnership and cost structure. This model has made us clearly to manage the company.